Software Design Criteria for Maintainability - Deraman, Aziz; P. J., Layzell (Universiti Putra Malaysia Press, 1995)
One of the current issues in the software engineering community is related to problems of software maintenance. It is a common belief that these problems are caused by bad software design and poor maintenance practices. The first of these is the concern of this paper. We argue that the existing software design methodologies are not properly developed based on criteria for easy software maintenance at later stages. Therefore, with a set of software design criteria for maintainability, software is believed to be more maintainable. In this paper we shall identify those criteria followed by assessment of several software design methodologies.